2010
DOI: 10.1021/jp905561n
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Investigation of Structure and Stability of Gen and GenNi (n = 1−20) Clusters: Validity of the Electron Counting Rule

Abstract: Structure and electronic properties of neutral and cationic pure and Ni-doped Ge clusters containing 1-20 Ge atoms are calculated within the framework of linear combination of atomic orbitals density functional theory. It is found that in clusters containing more than 8 Ge atoms the Ni atom is absorbed endohedrally in the Ge cage. Relative stability of Ni-doped clusters at different sizes is studied by calculating their binding energy, embedding energy of a Ni atom in a Ge cluster, highest-occupied molecular o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 55 publications
8
78
0
1
Order By: Relevance
“…We adopt a Gupta's many body potential [23] to calculate the cohesive energies of Al n and NiAl n clusters; (2) considering all of the possible Al n [1,2] and NiSi n , and NiGe n [24][25][26] cluster structures; (3) substituting one Al atom by Ni atom or adding one Ni atom to the isomers of the optimized Al clusters; (4) handmade structures following chemical intuition which consider a certain symmetry. In all, more than 400 configurations were selected.…”
Section: Computational Detailsmentioning
confidence: 99%
“…We adopt a Gupta's many body potential [23] to calculate the cohesive energies of Al n and NiAl n clusters; (2) considering all of the possible Al n [1,2] and NiSi n , and NiGe n [24][25][26] cluster structures; (3) substituting one Al atom by Ni atom or adding one Ni atom to the isomers of the optimized Al clusters; (4) handmade structures following chemical intuition which consider a certain symmetry. In all, more than 400 configurations were selected.…”
Section: Computational Detailsmentioning
confidence: 99%
“…A filled electron shell configuration will be related to the stability features of clusters based on the JSM theory, [34] in which the valence electrons can be assumed to freely itinerant in a simple mean-field potential formed by the nuclei of atoms, and fill the spherical shell orbitals of a cluster according to the orbital pattern of 1S 2 1P 6 1D 10 2S 2 1F 14 2P 6 1G 18 2D 10 , and so forth. As a result, these electrons of 8,18,20,34,40,58,68, and so forth are proposed to be the magic numbers that correspond to the spherically shell-closed electrons. [71] At present, let us turn our attention to the electron shell configuration of the Si 3 GeNb 1 cluster with C 3v symmetry.…”
Section: Electronic Structuresmentioning
confidence: 99%
“…Semiconductor silicon and germanium clusters are still an exciting research area and have been extensively investigated both experimentally and theoretically, because these clusters can act as a tunable building block to realize miniature nano‐devices by self‐assembly, with purpose to build up the novel nanomaterials applied in microelectronics industry . However, pure semiconductor clusters favor the sp 3 hybridization, and are chemically reactive due to the existence of unsaturated dangling bonds, resulting in the formation of unstable cage structures .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Many studies have demonstrated that the structure and stability of clusters sensitively vary with the atomic composition and concise number of electrons. [6][7][8][9][10][11][12][13][14] Nowadays, computational tools have effectively supported in studying the geometrical and electronic structures as well as chemical nature of the clusters which help to discover the mechanism of synthesizing new materials. On the other hand, small metal doped germanium clusters have been found to be the building blocks for some new types of metal and inorganic compounds.…”
Section: Introductionmentioning
confidence: 99%